Google Quiz Sebagai Alternatif Perangkat Digital Dalam Evaluasi Pembelajaran - Deni Sapta Nugraha; Wakhid Nashruddin (Politeknik Penerbangan Indonesia Curug, 2020)
The aim of this study is to uncover three main research questions dealing with the implementation of online quiz. This study was examined and analyzed descriptively by using a questionnaire as a research instrument, with one open-ended item. Results showed that the participants have positive attitudes toward the application. According to them, it is interesting, practicable, and user friendly. In other hand, there are some challenges that need to be coped with. Applying Google Quiz needs more time in preparation, it needs digital tool like computer or hand phone and also limited internet connection will cause the test unrecorded perfectly.